Correlation of Body Mass Index and age with Mild Cognitive Impairment (MCI) in elderly of Guwahati City, Assam - Vinoth Rajendran; Anku Moni Saikia; Mintu Dewri Bharali (Medsci Publications, 2023)
Objective: To determine the correlation between BMI and age with MCI and  after stratifying for BMI and socio-demographic characteristics. Methods: This cross-sectional study was conducted among 576 elderly (≥60 years) in Guwahati city using a multi-stage sampling technique. Hindi Mini-Mental State Examination tool was used for screening for dementia and MCI. Data were collected using a pre-designed and pre-tested schedule and SPSS was used for analysis. Results: HMMSE scores were not significantly correlated with BMI (r =0.07). However, when stratified, a significantly negative correlation of BMI with HMMSE scores was seen for illiterates (r =-0.21), primary school education (r =-0.48) and unskilled workers (r =-0.49). There was a significant negative correlation between age and cognition for elderly belonging to  OBC, (r =-0.21), Lower middle (III), (r =-0.39), Upper Lower (r =-0.17),  Lower (V), (r =-0.26), Graduate, Post Graduate,(r = -0.23), Middle School, (r =-0.36), Illiterate, (r =-0.34), Clerical, (r =-0.60), Semi Professional, (r =-0.62), skilled worker (r=-0.68), Unemployed,  (r =-0.15) and Obese, (r =-0.30). Conclusion: Various factors like age, category, socioeconomic status, and Body Mass Index (BMI) were found to be predictors of cognition among the elderly.Further studies are needed to evaluate the correlations between age, BMI, and cognitive decline.